TREND DESIGN HIJAB DAN PERSEPSI HARGA TERHADAP KEPUTUSAN BELI HIJAB (KASUS PADA MAHASISWI UNIVERSITAS BAKRIE JAKARTA) - Hatta, Holila; Iswanty, Andriana Nabila (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
The research was conducted using a quantitative approach and an online survey involving 150 hijab users as samples. Purposive sampling method is intentionally set according to research needs. Researchers used google form addressed to female students as hijaber at Bakrie University. The analysis was carried out by multiple linear regression, which was previously pre-test and test for normality, validity and reliability with software SPSS Statistic.  The results showed that product design and each price variable had a significant influence on purchasing decisions. Then together the product design and price variables also have a significant influence on the variable purchase decision.